Potato contract farming and ‘privileged spaces’: preliminary insights from rural Maharashtra - Vicol, Mark (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
The emergence of modern value chain schemes such as contract farming in rural India is exposing households to new forms of agricultural production. Evidently, the spread of such schemes in India will have spatial implications for rural development. This short communication offers preliminary insights of the contours of these spatial implications from a case study of potato contract farming in three villages in Maharashtra, India. It is proposed that studies that combine a local-scale livelihoods approach with global value chain analysis can strengthen understanding of agricultural change and rural development by grounding value chain analysis in the place-based everyday realities of rural households. Using this approach to adopt an evolutionary view of livelihoods and value chains will lead to a much deeper understanding of possible future development pathways for rural households under conditions of agricultural transformation.